Philippines : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper highlights the Philippine growth performance led by the services sector. Average GDP growth is higher in the post-Asian crisis period in the Philippines, while the majority of the Philippines's regional peers have experienced substantially lower growth in the post-Asian crisis period compared with the pre-crisis period. Trade and transport, storage, and communications services have been growth drivers while private and financial services have started to add new momentum. Various transfer programs are identified that would be much better targeted than across-the-board energy tax cuts.